2009
DOI: 10.1007/s12282-009-0155-3
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in Singapore: some perspectives

Abstract: Breast cancer is the commonest malignancy among Singapore women, accounting for 29.7% of all female cancers, with an age-standardized rate of 54.9 per 100,000 per year. It has been the most frequent cancer in Singapore women for the last 30 years, with the highest rates previously reported in those aged between 45 and 49 years, but with a more recent observation of a change in peak age group to women in their late 50s. About 1,100 new cases are diagnosed annually and approximately 270 women die in Singapore ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Recent studies show that, similar to the countries and regions that had rapid socioeconomic growth, western lifestyle, mental stress or anxiety, early age at menarche, late age at menopause, non-breastfeeding and the history of benign breast diseases might be the risk factors for the higher incidence rate of breast cancer in urban Beijing [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies show that, similar to the countries and regions that had rapid socioeconomic growth, western lifestyle, mental stress or anxiety, early age at menarche, late age at menopause, non-breastfeeding and the history of benign breast diseases might be the risk factors for the higher incidence rate of breast cancer in urban Beijing [15][16][17][18] .…”
Section: Discussionmentioning
confidence: 97%
“…Breast cancer is one of the most frequently diagnosed cancers in women [13], and the mortality rate was high in the worldwide women [14,15]. It is well-established that breast cancer was induced by many endogenous and exogenous factors, such as the level of hormone, the capacity to repair damaged DNA, and different genetic background [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a Singapore study looking at women with breast cancer, the screening program, BreastScreen Singapore, adopted several factors including weekly multidisciplinary review sessions, to improve breast cancer detection rates [33]. It was discussed that there are logistical and cost barriers to implement collaboration.…”
Section: The Tumor Board Review: Online/offlinementioning
confidence: 99%
“…It was reported that more specialized surgeons participated in a greater amount of collaborative communication because they were more willing and/or had greater opportunities to invest in same day appointments and weekly tumor board meetings. Surgeons with a smaller breast cancer patient load would better benefit from virtual tumor boards [32,33].…”
Section: The Tumor Board Review: Online/offlinementioning
confidence: 99%